PERKEMBANGAN PENDIDIKAN SUKU AKIT DI DESA SUNGAI UPIH KECAMATAN KUALA KAMPAR KABUPATEN PELALAWAN - T. Nazri Supian; Isjoni Isjoni; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Education is humans need as long as humans live, without education humanlife willbe not develop and willbe left behind. ForIndonesian people, education is the best effortto educate the life of nation, as the goals of national education that stated in the 1945Constitution. Educational institutions (formal, non-formal, or informal) are places for thetransfer of knowledge and cultures (civilizations). The aims of this study was to determinethehistorical developments of the Akit tribe which is currently located at Sungai Upih village, tofind out the perceptions of the Akit tribe towards the educationat Sungai Upih village, to findout the population structure developmentsaccording to the education of theAkit tribe at SungaiUpih village, to find out the schools developments at Sungai Upih village, and to find out thesupporting factors and obstaclefactors towards the education of the Akit tribe at Sungai Upihvillage.This study was used qualitative and quantitative methods. All of the desirable data werecollected, clarified the alternative answers to respondents using qualitative descriptive analysistechniques, presented the data in tabular form, providedexplanations, and drewconclusions.This study was located at Sungai Upih village. Based on the results of this study,there are severalperceptions of the Akit tribe that are useful in developing education andseveral efforts that undertaken by the educational institutions towards the education of the Akittribe people, such as providing free schools, tuition assistance and others in order to bemotivated to continue the next level of education for children of the Akit tribe.Key Words: Education Development and Akit Tribe